Onko urheilijan ajattelutavalla merkitystä menestymiseen ja motivaatioon? : valmentajien näkemyksiä urheilussa menestymiseen vaikuttavista tekijöistä - Viklund, Netta (2024)
The purpose of this master's thesis has been to investigate coaches' perspectives on factors influencing athletes' success. The aim was to explore coaches' views, particularly on the significance of mindset in sports success and its connection to motivation. The topic was chosen due to its relevance. For instance, the High-Performance Sports Transformation Group initiated the development work of Athlete Pathways in 2011, which is still ongoing. The Athlete Pathway describes how the journey of an athlete aiming for the top should ideally be constructed in the sport. Additionally, the mindset and well-being of young athletes are currently very relevant topics. An example of this is the "Nuori mieli urheilussa" (Young Mind in Sports) project by the Mieli Association.